RECOGNITION THROUGH LETTERS AND NUMBERS ON THE INTERNET AGE CHILDREN USING KINDERGARTEN HTML AND VBSCRIPT - Deni Irawan; Ir. Don Elsyafitra (Jurnal Sistem Informasi, 2002)
In introducing the letters and numbers, we need a way to provide comfort and fun tochildren. Today many media that enable children belajr recognize letters and numberswhile playing, so that children can learn with a comfortable and enjoyable. Throughthis media, electronic media, namely computer expected.Internet has been very commonly used. Not only the office-office, but also homeschooland school-house, even today, the internet has been a lot of rentals areeverywhere. The Internet also is not only used by adults, but children also can use theInternet as a means of education and information for him, one by introducing lettersand numbers for them via the internet.For that, need an application to introduce letters and numbers to children that can beused diinternet, so kids can get used to interacting with computers since the early thanthey learn about letters and numbers. The application development was theintroduction of letters and numbers using HTML and VBScript.